Surface Modification of LaNi0.6Fe0.4O3-δ Film Electrode by Ce0.9Gd0.1O1.95 Porous Layer. (13th April 2015) - Budiman, Riyan Achmad; Miyazaki, Takamichi; Hashimoto, Shin-ichi; Yashiro, Keiji; Amezawa, Koji; Kawada, Tatsuya
Abstract : The Ce0.9 Gd0.1 O1.95 porous layer was deposited into the top of LaNi0.6 Fe0.4 O3-δ film electrode and compared to the bare LaNi0.6 Fe0.4 O3-δ film electrode to determine the surface oxygen exchange rate. The measurement has been done by electrochemical impedance spectroscopy and isotope exchange experiment under various temperatures and oxygen partial pressures. The surface oxygen exchange rate of LaNi0.6 Fe0.4 O3-δ film - Ce0.9 Gd0.1 O1.95 porous layer was enhanced compared to the bare LaNi0.6 Fe0.4 O3-δ film electrode. The role of Ce0.9 Gd0.1 O1.95 was the promotion of incorporation step on the oxygen reduction process in the electrode as the reason of the enhancement of surface oxygen exchange rate. An Auger electron spectroscopy measurement has been done to investigate the compositional change at the LaNi0.6 Fe0.4 O3-δ film surface. No compositional change was observed on the LaNi0.6 Fe0.4 O3-δ film surface which can be associated to the enhancement of surface oxygen exchange rate.